Digital government: Social media as a mediator in technology acceptance with political knowledge, interest, and participation - Tin Tin Ting; Mei Yuen Lee; Shu Xuan Chok; Yun Hung Huang; Xian Ni Choy; Kuok Tiung Lee; Omolayo M. Ikumapayi; Temitope Olumide Olugbade (Bastas Publications DOO, Montenegro, 2024)
Social media is an essential tool for governments to spread political information in the digital era. However, the influence of social media on political participation is significant but not well recognised in developing countries such as Malaysia. The main problem is the lack of clarity surrounding the factors that influence citizen adoption of political social networks and how this influences political interest, knowledge, and participation. The purpose of this study is to explore factors and social media as mediator in political dynamics. The study sampled 338 young people from the University Malaysia Sabah using convenient sampling. The online questionnaire is distributed through Google Form and the hypotheses are analysed using SPSS Process macro and AMOS. The results highlighted that perceived usefulness, perceived ease of use, perceived enjoyment, political participation, and political interest are significantly related to governmentpolitical related social media usage. Social media usage mediated the relationship between all predictors and dependent variables (except for political knowledge). This study offers evidencebased suggestions within a theoretical framework to improve the government’s use of social media for civil engagement.